Riqueza específica y determinación de la diversidad de las aves rapaces de los ríos Yaqui y Bavispe, en Sonora, México - Rodríguez, Ricardo; Brown, Bryan T. (Instituto de Ecología, A.C., 1990)
A canoe trip was conduted, in the early spring of 1987 and 1988, throughout the river Rio Yaqui and one of its tributaries, the Rio Bavispe, situated in Sonora, Mexico. Eleven and seven raptor species were recorded throughout the river in 1987 and 1988, respectively. Species diversity values were similar among rivers and among year, although the proportions of the most abundant species varied considerably from year to year. Raptor species occupied different riparian habitats, but most of them are relative specialists in their habitat use. The relationships between habitat and activities are also discussed.